2020
DOI: 10.3389/fonc.2020.01059
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology of Ground Glass Opacity Lung Adenocarcinoma: A Network-Based Cumulative Meta-Analysis

Abstract: Introduction: Due to the introduction of low-dose computed tomography (CT) and screening procedures, the proportion of early-stage lung cancer with ground glass opacity (GGO) manifestation is increasing in clinical practice. However, its epidemiological characteristics is still not fully investigated. Methods: We retrieved all solitary GGO adenocarcinoma lung cancer (ADLC) on the PubMed, Cochrane Library, and Embase databases until January 1, 2019 and extracted the general information to perform the meta-analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 63 publications
2
5
0
Order By: Relevance
“…Lung cancer is one of the most common causes of cancer death, and tobacco smoking is the most well-known risk factor for lung cancer [ 1 ]. The incidence of lung cancer among never-smokers has been increasing over the past decade, and exposure to secondhand tobacco smoke, radon, and/or air pollution is considered to be a possible etiological factor [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lung cancer is one of the most common causes of cancer death, and tobacco smoking is the most well-known risk factor for lung cancer [ 1 ]. The incidence of lung cancer among never-smokers has been increasing over the past decade, and exposure to secondhand tobacco smoke, radon, and/or air pollution is considered to be a possible etiological factor [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, Li et al. found the average age at diagnosis had significantly decreased from 66.40 to 59.06 in the past two decades using a cumulative meta-analysis ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings showed age was a key factor for risk of malignance consistent with Zhang's study. Besides, Li et al found the average age at diagnosis had significantly decreased from 66.40 to 59.06 in the past two decades using a cumulative meta-analysis (8).…”
Section: Discussionmentioning
confidence: 99%
“…Technological advancement in medicine has evolved rapidly, with low-dose computed tomography (LDCT) screening, the discovery of multifocal lung cancer, incidental ground-glass opacity (GGO), and early-stage lung cancer becoming increasingly common [1,2]. Incidental GGO can be risk of malignant precursor or early-stage lung malignancy in up to 63% of cases [3][4][5][6], bringing new management challenges especially because of multifocal tendency. Lung resection remains the gold standard for treatment of early-stage nonsmall cell lung carcinoma (NSCLC) [7], however 20% of patients are not suitable for lung resection due to multiple comorbidities and poor cardiopulmonary reserve [8,9].…”
Section: Introductionmentioning
confidence: 99%